Applying Merdeka Belajar in non-formal curriculum at PKBM Rumbai Koteka - Rif’an Efendi; Priadi Surya; Tarso Tarso; Rohmanur Mala (Universitas Pendidikan Indonesia, 2025)
Non-formal education plays a crucial role in providing access to learning for communities that are not served by the formal education system. This study aims to analyze the implementation of the Merdeka Belajar policy within the non-formal education curriculum at PKBM Rumbai Koteka. The research employs a qualitative descriptive approach, involving subjects such as administrators, tutors, learners, and alumni of the equivalency program. Data were collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, presentation, verification, and conclusion drawing. The findings indicate that the curriculum at PKBM Rumbai Koteka reflects the principles of the Kurikulum Merdeka, which emphasizes flexibility, adaptability, and a learner-centered approach. Curriculum development follows the five-asset approach: human, natural, social, financial, and physical assets. Teaching modules are designed to replace traditional lesson plans and support independent learning. Implementation is carried out through intra curricular learning and project-based activities aligned with the Pancasila Student Profile and practical skills. Evaluation is conducted periodically using formative and summative assessments to ensure curriculum relevance. Overall, the Merdeka Belajar policy promotes contextual learning and cultivates independence, creativity, and student readiness to address global challenges. Abstrak Pendidikan nonformal memiliki peran strategis dalam menyediakan akses pembelajaran bagi masyarakat yang tidak terjangkau oleh sistem pendidikan formal. Penelitian ini bertujuan untuk menganalisis implementasi kebijakan Merdeka Belajar dalam kurikulum pendidikan nonformal di PKBM Rumbai Koteka. Penelitian ini berpendekatan deskriptif kualitatif dengan subjek penelitian meliputi pengelola, tutor, peserta didik, dan alumni program kesetaraan. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Analisis data dilakukan melalui reduksi, penyajian, verifikasi, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa kurikulum di PKBM Rumbai Koteka mencerminkan prinsip Kurikulum Merdeka, yaitu fleksibel, adaptif, dan berpusat pada siswa. Pengembangan kurikulum menggunakan pendekatan lima asset seperti manusia, alam, sosial, finansial, dan fisik. Modul ajar disusun sebagai pengganti RPP untuk mendukung pembelajaran mandiri. Implementasi dilakukan melalui pembelajaran intrakurikuler dan proyek berbasis karakter Profil Pelajar Pancasila serta keterampilan praktis. Evaluasi dilaksanakan secara berkala dengan asesmen formatif dan sumatif untuk menjamin relevansi kurikulum. Secara keseluruhan, kebijakan Merdeka Belajar mendukung pembelajaran yang kontekstual, mendorong kemandirian, kreativitas, dan kesiapan peserta didik menghadapi tantangan global. Kata Kunci: kurikulum; Merdeka Belajar; PKBM; pendidikan nonformal